Government effectiveness in the provision of public goods: The role of institutional quality - Puneet Arora; Alberto Chong (Journal of Applied Economics, 2018)
While poorer countries have a much smaller public sector and correspondingly a smaller tax burden than richer countries, their economic performance has not been necessarily better. This paper discusses the role that institutional quality plays in determining government's effectiveness in delivering public goods and in, therefore, mediating the effects of higher taxation in an economy. A simple theoretical model shows that provision of public goods and optimal tax levels increase with improved institutional quality. Using firm-level perceptions data on the quality of public services and the tax burden, consistent with the predictions of our model, we find that a higher level of institutional quality bolsters positive perception of the quality of public services while at the same time moderating the view of the taxes as an obstacle to growth.
Keywords: 330; development; Institutions; quality of public services; regulation; taxes